2019
DOI: 10.3390/nu11081835
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia Changes Expression of Key Adipogenesis Markers (C/EBPα and PPARᵞ)and Morphology of Differentiating Human Visceral Adipocytes

Abstract: Disturbances in adipose tissue significantly contribute to the development of metabolic disorders, which are connected with hyperglycemia (HG) and underlain by epigenetics-based mechanisms. Therefore, we aimed to evaluate the effect of hyperglycemia on proliferating, differentiating and maturating human visceral pre/adipocytes (HPA-v). Three stages of cell culture were conducted under constant or variable glycemic conditions. Adipogenesis progress was assessed using BODIPY 505/515 staining. Lipid content typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…Therefore, the inhibition of IL-6 transcription could be protective for C/EBPα expression and Ads commitment. Consistently, transcription of CEBPA was opposed to the IL-6 mRNA levels in this model, whereas chronic HG accelerated adipogenesis, as we reported previously [18]. On the other hand, Chinese researchers described a gradual increase in IL-6 production during adipogenic differentiation in human bone marrow mesenchymal stem cells (BM-MSCs), while we observed increased IL-6 production in mature Ads [19].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, the inhibition of IL-6 transcription could be protective for C/EBPα expression and Ads commitment. Consistently, transcription of CEBPA was opposed to the IL-6 mRNA levels in this model, whereas chronic HG accelerated adipogenesis, as we reported previously [18]. On the other hand, Chinese researchers described a gradual increase in IL-6 production during adipogenic differentiation in human bone marrow mesenchymal stem cells (BM-MSCs), while we observed increased IL-6 production in mature Ads [19].…”
Section: Discussionsupporting
confidence: 90%
“…The most important stage of differentiation requiring the glucose pulse was also assessed using a design reflecting our transient HG exposure, but with contrasting results [32]. Indeed, the authors observed around 75% lower lipid accumulation in 4 mM of glucose, and, previously, we had consistently observed that HG accelerated adipogenesis [18]. Thus, more research is needed to explore the concentration of glucose dysregulating adipokines and Ads metabolism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The complete list of 78 miRNAs and 4 small nuclear RNAs (snRNAs) is provided in Table S1 . Selection of the set of molecules was based on: (i) preliminary data obtained via previously used TLDA cards on 1 healthy and 1 diabetic subject, (ii) literature search for miRNAs associated with T2DM, IR, obesity in all insulin-responsive tissues, (iii) providing a broad panel of candidate reference genes (literature search), (iv) results of our previous research on hyperglycemia-exposed visceral pre/adipocytes [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…IRS binds to the kinase regulatory subunit of PI3K (PI3K-R), the central molecule of the pathway. This, in turn, causes activation of the catalytic PI3K (PI3K-C) subunit that converts phosphatidylinositol (4,5)-biphosphate (PIP2) to phosphatidylinositol (3,4,5)-triphosphate (PIP3) [8]. The main insulin pathway regulator, PTEN, (phosphatase and tensin homolog), inhibits further signal transduction by PIP3 dephosphorylation [10].…”
Section: Introductionmentioning
confidence: 99%